PTH-093 Chromogranin-a : Can It Predict Radiological Progression In Neuroendocrine Tumours?. (9th June 2014) - Rossi, RE; Garcia-Hernandez, J; Martin, NG; Mullan, M; Meyer, T; Thirlwell, C; Watkins, J; Caplin, ME; Toumpanakis, C
Abstract : Introduction: Chromogranin A (CgA) is considered as the best general marker for the diagnosis and follow-up of neuroendocrine tumours (NETs) and is also of prognostic value. In literature, there are no available studies which analysed the role of CgA as a predictor of radiological disease progression in all NETs. Present study investigates the prognostic value of CgA as a predictor of radiological disease progression in NET patients. Methods: Patients with metastatic NETs and evidence of Radiological Progression (RP) according to RECIST 1.1 were identified from a NET database. Plasma CgA were measured 6 and 12 months before RP and at the event of RP. CgA was measured with the Supra-regional-Assay-Service radioimmunoassay (Hammersmith Hospital), normal value <60 pmol/L. The tumours were graded according to the 2010 WHO classification, as G1 (Ki67 <2%), G2 (Ki67: 2–20%), G3 (Ki67 >20%). Results: 152 patients were evaluable including 91 midgut NET and 61 pancreatic NETs (PNETs). Of these, 56 were G1 NETs, 65 G2, 10 G3, 21 of unknown histology. 95.4% of the patients had liver metastases, whereas bone and lung metastases were present in a smaller proportion of patients (27.6 and 9.9%, respectively). Median CgA for all NETs 6 months before RP was 213 pmol/L [Interquartile 1 (Q1)=67 and 3 (Q3)=664.5 pmol/L] compared to 166 pmol/L (Q1 52, Q3 535 pmol/L) one year before RP, T = 598.5, p = 0.07. Significant results were found for PNETs [median CgA 6 months before RP: 100 pmol/L (Q1 53, Q3 286.25 pmol/L) and at 12 months: 52 pmol/L (Q1 36.25, Q3 128 pmol/L), T=52, p = 0.048], but not for midgut NETs [median CgA 6 months before RP: 389.5 pmol/L (Q1 131.5, Q3 791.5 pmol/L) and at 12 months: 319 pmol/L (Q1 158, Q3 753 pmol/L), T=191, p = .39]. Both midgut and PNETs CgA values were significantly higher at RP than 12 months before [267 pmol/L (Q1=66, Q3=777) vs. 166 pmol/L (Q1=52, Q3=535), T= 394.5, p = 0.03]. Overall, G1 tumours had median CgA value at 6 months significantly higher than at 12 months [181(Q1=56.25, Q3=624) vs. 149.5 pmol/L (Q1=44, Q3=247.25), T=70, p = 0.048]. Conclusion: CgA seems to have predictive value 6 months prior to RP for PNETs and G1 tumours, which may be of value to identify specific subgroups of patients who may benefit from a more aggressive follow-up with possible early intervention in case of increased CgA levels. Further prospective studies are needed to enable more definitive conclusions. References: 1 Oberg K et al . Pancreas 2011 2 Ter-Minassian M et al . Endocr Relat Cancer 2013 3 Welin S et al . Neuroendocrinology 2009 4 Jensen KH et al . Scand J Gastroenterol 2013 Disclosure of Interest: None Declared.